Stimulating community action for suicide prevention: findings on the effectiveness of the Australian R U OK? campaign - Mok, K.; Donovan, Robert; Hocking, B.; Maher, B.; Lewis, R.; Pirkis, J. (The Clifford Beers Foundation, 2016)
R U OK? is an Australian-based organisation that aims to prevent suicide by empowering and encouraging community members to have regular, meaningful conversations with those around them by asking, ‘Are you ok?’ One of the organisation’s main activities is ‘R U OK? Day’, a national day of action held in Australia every year to remind people of the importance of connecting with and supporting those around them who may be troubled. This paper primarily examines data from a 2014 Australia-wide population survey evaluating the effectiveness of the R U OK? campaign in promoting its message. Following R U OK? Day in 2014, approximately two-thirds of participants reported being aware of R U OK?, with one in five of these participating in R U OK? Day activities. Overall, people believed that the R U OK? campaign has a positive impact on people’s willingness to talk to others about their problems and seek professional help, and in reducing the stigma associated with help-seeking. The findings were positive, but future work should also investigate outcomes such as knowledge, stigma and help-seeking in order to demonstrate the efficacy of the campaign.